Prevalence of Alcohol Consumption among Primary and Secondary School Adolescents in Obiaruku Community in Delta State, Southern Nigeria (African Journal of Biomedical Research, 2020)
Consumption of alcohol by underage teenagers and adolescents is a major public health problem confronting many developing countries including Nigeria. Studies have shown the increasing rate of alcohol consumption among these high risk groups. The objective of the study was to determine the prevalence of alcohol use among Primary and Secondary School teenagers in Obiaruku Community. The study employed a descriptive cross sectional study among pupils and students in primary and secondary schools in Obiaruku community. The study utilized random sampling technique in selecting 326 pupils and students from both primary and secondary schools in Obiaruku community. The instrument for data collection was a semi- structured questionnaire. The collected data was analysed with SPSS version 21 and presented in percentages and frequencies, with Chi-Square used to analysed association between demographic characteristics and prevalence of alcohol with level of significance set at P